2023
DOI: 10.3847/1538-4357/aca893
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Scales of Complexity and Coherence within Interplanetary Coronal Mass Ejections: Insights from Spacecraft Swarms in Global Heliospheric Simulations

Abstract: Many aspects of the 3D structure and evolution of interplanetary coronal mass ejections (ICMEs) remain unexplained. Here, we investigate two main topics: (1) the coherence scale of magnetic fields inside ICMEs, and (2) the dynamic nature of ICME magnetic complexity. We simulate ICMEs interacting with different solar winds using the linear force-free spheromak model incorporated into the EUHFORIA model. We place a swarm of ∼20,000 spacecraft in the 3D simulation domain and characterize ICME magnetic complexity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…None of these events present MC-like signatures at both spacecraft (CMEs 5 and 12 are MC-like at STEREO-A only) and performing an analysis of the correlation between the magnetic field measurements as done in Lugaz et al (2018) would be meaningless since the measurements are too different. Overall, this indicates that past estimates of the ME coherence of ∼20° (Lugaz et al 2018;Scolini et al 2023) may be an upper bound for the true coherence length. We note that, based on the analysis of Owens et al (2017), an ME with an angular width of 20°should be coherent if Alfvén waves are the carrier of information across the ME.…”
Section: Cme Angular Size In the Eclipticmentioning
confidence: 79%
See 1 more Smart Citation
“…None of these events present MC-like signatures at both spacecraft (CMEs 5 and 12 are MC-like at STEREO-A only) and performing an analysis of the correlation between the magnetic field measurements as done in Lugaz et al (2018) would be meaningless since the measurements are too different. Overall, this indicates that past estimates of the ME coherence of ∼20° (Lugaz et al 2018;Scolini et al 2023) may be an upper bound for the true coherence length. We note that, based on the analysis of Owens et al (2017), an ME with an angular width of 20°should be coherent if Alfvén waves are the carrier of information across the ME.…”
Section: Cme Angular Size In the Eclipticmentioning
confidence: 79%
“…Regarding CME models, we note that, under the flux rope paradigm, if the CME leg-to-leg angular extent is comparable to the nonradial cross section, flux rope models would need to be significantly modified to account for the CME major radius of curvature and the magnetic flux balance within a thick flux rope. The angular extent is also a critical quantity to investigate ME coherence, an area of recent focus in CME studies (Owens et al 2017;Scolini et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Interplanetary coronal mass ejections (ICMEs; Bothmer & Schwenn 1998;Cane & Richardson 2003;Kilpua et al 2017) are said to be "coherent" if they are capable of responding to external perturbations in a collective manner (Burlaga et al 1981;Owens et al 2017). Whether ICMEs behave coherently at global or only at local scales is a topic of debate (see, e.g., Lugaz et al 2018;Owens 2020;Al-Haddad et al 2022;Scolini et al 2023) due to its implications for the global evolution of ICME magnetic structures and the interpretation of single-point in situ measurements. Throughout this work, we use the term "magnetic ejecta" (ME; Winslow et al 2015) to refer to the magnetically dominated portion of an ICME, which is identified by an enhanced magnetic field and low levels of magnetic fluctuations compared to the preceding and following interplanetary magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to date, such observational studies have only been possible near 1 au, due to the lack of spacecraft reaching close angular separations at inner heliocentric distances prior to the current solar cycle. In an attempt to overcome these observational limitations, in Scolini et al (2023) we performed 3D numerical simulations of ICMEs in the inner heliosphere, highlighting the role of interactions with other large-scale structures, such as high-speed streams (HSSs) and stream interaction regions (SIRs), as a primary mechanism acting to decrease the correlation scale of the magnetic field components within ICMEs. This study revealed how, in such cases, the correlation is progressively lost by ICMEs during propagation between 0.1 and 2 au.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning their magnetic flux, it can be reduced due to magnetic reconnection, which will lead to magnetic erosion at the front of the ICME (Dasso et al 2007;Ruffenach et al 2012). As they propagate, ICMEs are more likely to become more and more complex as a result of their interaction with solar wind structures (Winslow et al 2015(Winslow et al , 2022Scolini et al 2022Scolini et al , 2023, and to display aging processes that will contribute to their deformation (Démoulin et al 2020). They will also change as a result of interactions with specific structures, such as high-speed streams (HSSs; Fenrich & Luhmann 1998;Heinemann et al 2019;Scolini et al 2021b), stream-interaction regions (SIRs) or other ICMEs (Lugaz et al 2005;Scolini et al 2020).…”
Section: Introductionmentioning
confidence: 99%